Langkah Spiritual: Pendekatan Metodologis Menuju Puncak Capaian Sufistik - Br, A. Nurhidayah; Syamsuddin, Darussalam (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study aims to analyze of Sufism as a methodological approach to achieving the pinnacle of spiritual attainment. A library research approach was employed, utilizing descriptive, interpretative, and analytical methods. Data were sourced from primary references, including books and Sufi literature, as well as secondary sources like relevant journal articles. The analysis focuses on applying Sufi concepts to guide individuals toward inner peace and closeness to God. The findings show that the Sufi stages of takhalli, tahalli, and tajalli are key to the spiritual journey. Spiritual practices such as dhikr, muraqabah, suluk, riyadhah, and tafakur play a central role in this process, not only cleansing the heart of negative traits but also instilling noble values like justice, divine love, and patience. The ultimate achievements of Sufism-mahabbah (love for God) and ma’rifah (knowledge of God)-bring individuals to the highest level of spiritual closeness. In the modern era, Sufism offers a holistic approach to addressing the pressures of materialistic life while fostering inner tranquility through divine connection. This study highlights the universal significance of Sufi teachings as a guide for human spiritual development.